2019
DOI: 10.5327/z1679443520190439
|View full text |Cite
|
Sign up to set email alerts
|

Trend in the incidence of commuting accidents among workers in Brazil between 2009 and 2016

Abstract: | Background: Commuting accidents might have serious consequences for the health of workers, in addition to considerable financial impacts on the national health system and the social security administration. Objective: To describe the epidemiological profile and calculate the incidence of commuting accidents in Brazil in the period from 2009 to 2016. Methods: Retrospective and descriptive study with time series analysis (2009-20… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 8 publications
(19 reference statements)
1
4
0
Order By: Relevance
“…These accidents, considered a serious national public health issue, involve various segments of the society such as the employer/company, the affected worker and his or her family, the Brazilian social security, and the Unified Health System (SUS). 26 , 27 In the present study we observed a mean number of 745 occupational accidents reported per year in the analyzed period. Based on the study by Almeida and Barbosa-Branco 28 , which described a mean period of sickness leave due to a B91 occupational accident (ADAT-B91) of 75 days, 28 it is possible to estimate that, on average, 56 thousand workdays have been lost per year in Amapá between 2007 and 2017.…”
Section: Discussionsupporting
confidence: 53%
“…These accidents, considered a serious national public health issue, involve various segments of the society such as the employer/company, the affected worker and his or her family, the Brazilian social security, and the Unified Health System (SUS). 26 , 27 In the present study we observed a mean number of 745 occupational accidents reported per year in the analyzed period. Based on the study by Almeida and Barbosa-Branco 28 , which described a mean period of sickness leave due to a B91 occupational accident (ADAT-B91) of 75 days, 28 it is possible to estimate that, on average, 56 thousand workdays have been lost per year in Amapá between 2007 and 2017.…”
Section: Discussionsupporting
confidence: 53%
“…An increase in work-related traffic injuries over the years was reported from other countries as well, 39,40 but it was much less dramatic. For example, the increase in traffic injuries in Brazil between 2009 and 2016 was only 20% 40 . In Malaysia the increase was 49% over six years 39 .…”
Section: Discussionmentioning
confidence: 80%
“…15 Between 2000 and 2011, the number of deaths and crashes with injuries was declining. 15 An increase in work-related traffic injuries over the years was reported from other countries as well, 39,40 but it was much less dramatic. For example, the increase in traffic injuries in Brazil between 2009 and 2016 was only 20%.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“… 15 On the other hand, a national research showed an increasing trend in the incidence and number of commuting accidents in Brazil between 2009 and 2016. 16 Unlike typical accidents, commuting accidents occur during commuting to work and are often beyond the boundaries of organizational control due to external factors, such as weather conditions, vehicle conservation, other’s behavior in traffic, among others, making their prevention more challenging. The National Health Survey and the Violence and Accident Surveillance System for Urgency and Emergency Sentinel Services corroborate the relative stability of OA, accounting for about one-third of all national OA cases.…”
Section: Discussionmentioning
confidence: 99%